Pentingkah Peran Relawan Pajak dalam Mempengaruhi Peningkatan Kepatuhan Wajib Pajak Orang Pribadi? - Yusrifa Satriani Atmi Mustakim; Juli Ratnawati; Purwantoro Purwantoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the influence of the role of tax volunteers, tax socialization activities, and taxpayer awareness on the compliance of individual taxpayers. The sample consists of 100 individual taxpayers registered at the Semarang Tengah Tax Office, selected using a random sampling method. Data were collected through questionnaires and analyzed using SPSS version 25. The results indicate that the role of tax volunteers, tax socialization, and taxpayer awareness have a positive and significant effect on individual taxpayer compliance. These findings suggest that the presence of tax volunteers, effective tax socialization, and a high level of taxpayer awareness contribute to improved compliance among individual taxpayers. This study supports the Theory of Planned Behavior, which emphasizes the role of awareness as a form of perceived behavioral control. An individual’s behavior is influenced by the level of awareness and intention they possess. Future research is encouraged to include and examine additional variables that may affect taxpayer compliance.